The use of Faecal Microbiota Transplantation (FMT) in Europe: A Europe-wide survey - Baunwall, Simon Mark Dahl; Terveer, Elisabeth M.; Dahlerup, Jens Frederik; Erikstrup, Christian; Arkkila, Perttu; Vehreschild, Maria JGT; Ianiro, Gianluca; Gasbarrini, Antonio; Sokol, Harry; Kump, Patrizia K.; Satokari, Reetta; De Looze, Danny; et al. (The Lancet Regional Health - Europe, 2021)
Background: Faecal microbiota transplantation (FMT) is an emerging treatment modality, but its current clinical use and organisation are unknown. We aimed to describe the clinical use, conduct, and potential for FMT in Europe. Methods: We invited all hospital-based FMT centres within the European Council member states to answer a web-based questionnaire covering their clinical activities, organisation, and regulation of FMT in 2019. Responders were identified from trials registered at clinicaltrials.gov and from the United European Gastroenterology (UEG) working group for stool banking and FMT. Findings: In 2019, 31 FMT centres from 17 countries reported a total of 1,874 (median 25, quartile 10–64) FMT procedures; 1,077 (57%) with Clostridioides difficile infection (CDI) as indication, 791 (42%) with experimental indications, and 6 (0•3%) unaccounted for. Adjusted to population size, 0•257 per 100,000 population received FMT for CDI and 0•189 per 100,000 population for experimental indications. With estimated 12,400 (6,100–28,500) annual cases of multiple, recurrent CDI and indication for FMT in Europe, the current European FMT activity covers approximately 10% of the patients with indication. The participating centres demonstrated high safety standards and adherence to international consensus guidelines. Formal or informal regulation from health authorities was present at 21 (68%) centres. Interpretation: FMT is a widespread routine treatment for multiple, recurrent CDI and an experimental treatment. Embedded within hospital settings, FMT centres operate with high standards across Europe to provide safe FMT. A significant gap in FMT coverage suggests the need to raise clinical awareness and increase the FMT activity in Europe by at least 10-fold to meet the true, indicated need. Funding: NordForsk under the Nordic Council and Innovation Fund Denmark (j.no. 8056–00006B).
CRIS-Team Scopus Importer:2025-10-13
Keywords: Clostridioides difficile; Faecal microbiota transplantation; FMT; Stool banking